A swine model of intracellular cerebral edema – Cerebral physiology and intracranial compliance. (December 2018) - Ramirez de Noriega, Fernando; Manley, Geoffrey T.; Moscovici, Samuel; Itshayek, Eyal; Tamir, Idit; Fellig, Yakov; Shkara, Ramiz Abu; Rosenthal, Guy
Highlights: A swine model of cerebral edema leading to graded and sustained elevation of ICP is presented. ICP, CPP, and brain tissue oxygen tension cross clinically relevant thresholds. Intracranial compliance worsens with increasing brain edema and ICP dose rises. Electron microscopy demonstrates astrocytic foot process swelling. A platform to study the cerebral physiological profile with severe brain edema. Abstract: Cerebral edema leading to elevated intracranial pressure (ICP) is a fundamental concern after severe traumatic brain injury (TBI), stroke, and severe acute hyponatremia. We describe a swine model of water intoxication and its cerebral histological and physiological sequela. We studied female swine weighing 35–45 kg. Four serum sodium intervals were designated: baseline, mild, moderate, and severe hyponatremia attained by infusing hypotonic saline. Intracranial fluid injections were performed to assess intracranial compliance. At baseline and following water intoxication wedge biopsy was obtained for pathological examination and electron microscopy. We studied 8 swine and found an increase in ICP that was strongly related to the decrease in serum sodium level. Mean ICP rose from a baseline of 6 ± 2 to 28 ± 6 mm Hg during severe hyponatremia, while cerebral perfusion pressure (CPP) decreased from 72 ± 10 to 46 ± 11 mm Hg. Brain tissue oxygen tension (PbtO2 ) decreased from 18.4 ± 8.9 to 5.3 ± 3.0 mm Hg. Electron microscopy demonstrated intracellular edema and astrocytic foot process swelling following water intoxication. With severe hyponatremia, 2 cc intracranial fluid injection resulted in progressively greater ICP dose, indicating a worsening intracranial compliance. Our model leads to graded and sustained elevation of ICP, lower CPP, and decreased PbtO2, all of which cross clinically relevant thresholds. Intracranial compliance worsens with increased cerebral swelling. This model may serve as a platform to study which therapeutic interventions best improve the cerebral physiological profile in the face of severe brain edema.